Compliance with Antimicrobial Prophylaxis Guidelines in Endourological Procedures: Frequency and Related Outcomes - Abdaljaleel, Sondos; Abdeljalil, Mariam; Awwad, Oriana; Al Edwan, Ghazi; Amaireh, Mohammad; Hamdan, Manar; Khattab, Ahmad; Al-Hourani, Tasneem (Jordan Journal of Pharmaceutical Sciences, 2023)
Introduction: Surgical antimicrobial prophylaxis (SAP), when used appropriately based on evidence-based guidelines, reduces the rate of infectious complications following endourological procedures without compromising patient outcomes. Aims: to audit the appropriateness of the current SAP used in endourological surgeries based on international guidelines and report their associated outcomes (urinary tract infection (UTI) and bloodstream infection (BSI)). Methodology: The adherence to international guidelines recommendations; AUA 2019 and EAU 2020, regarding indication, duration, choice, and dose of the antibiotics used in endourological procedures were assessed in two medical centers in Amman/Jordan. Also, patients were asked to conduct laboratory urine test to determine the rate of infectious complications within one-month post-procedure. Results: Three hundred sixty-one patients were recruited for the study. The adherence rate to guidelines regarding indication, choice, and dose of pre-operative antibiotics was 90.3%, 2.8%, and 77.8% respectively. The duration was concordant with guidelines in only 3.4% of participants. A total of 41.8% of patients completed follow-up. Among those, 4.6% developed bacterial UTIs, and 0.7% developed BSI. Conclusion: Adherence to SAP guidelines in endourological procedures is far from optimal, especially by an inappropriate selection of broad-spectrum antibiotics as the agent of choice and prolonged use of antibiotics after the procedure in the absence of any documented infectious complication.